Mepitel Film for the Prevention of Acute Radiation Dermatitis in Breast Cancer: A Randomized Multicenter Open-Label Phase III Trial. Issue 6 (20th February 2023) - Behroozian, Tara; Milton, Lauren; Karam, Irene; Zhang, Liying; Ding, Keyue; Lou, Julia; Gallant, François; Rakovitch, Eileen; Tran, William; Soliman, Hany; Leung, Eric; Vesprini, Danny; et al.
Abstract : PURPOSE: Radiation dermatitis (RD) is common in patients undergoing breast radiotherapy. Mepitel film (MF) can reduce RD, but the results from two randomized controlled trials are conflicting. We aimed to conduct a confirmatory randomized controlled trial in patients at risk of RD. METHODS: Patients were randomly assigned to receive MF or standard care (2:1 ratio). Patients with large breasts after lumpectomy (bra size ≥ 36 inches or cup size ≥ C) or after mastectomy were eligible. Stratification factors included surgery type, dose fractionation, and administration of boost/bolus. The primary end point was grade (G) 2 or 3 RD using the Common Terminology Criteria for Adverse Events v5.0. Secondary end points included patient- and clinician-reported outcomes. RESULTS: Between January 2020 and May 2022, 376 patients were included in the modified intention-to-treat analysis. The incidence of G2 or 3 RD was significantly lower in MF patients compared with standard care (n = 39/251, 15.5%; 95% CI, 11.3 to 20.6% v n = 57/125, 45.6%; 95% CI, 36.7 to 54.8% respectively, odds ratio (OR): 0.20, P < .0001). Benefits of MF remained significant in patients who developed G 3 RD (n = 7, 2.8%; 95% CI, 1.1 to 5.7% v n = 17, 13.6%; 95% CI, 8.1 to 20.9%, OR: 0.19) and moist desquamation (n = 20, 8.0%; 95% CI, 4.9 to 12.0% v n = 24, 19.2%; 95% CI, 12.7 to 27.1%, OR: 0.36). When evaluating the combined patient and health care provider score using Radiation-Induced Skin Reaction Assessment Scale, the MF arm had significantly lower scores ( P < .0001). Individual items on the Radiation-Induced Skin Reaction Assessment Scale also favored the MF for both patient- and clinician-reported outcomes. Blistering/peeling, erythema, pigmentation, and edema were significantly reduced in the MF arm. Three patients removed the film prematurely because of rash (n = 2) and excessive pruritus (n = 1). CONCLUSION: MF significantly reduces RD in patients undergoing breast radiotherapy.